2014
DOI: 10.1186/1475-2840-13-68
|View full text |Cite
|
Sign up to set email alerts
|

Rapid onset of cardiomyopathy in STZ-induced female diabetic mice involves the downregulation of pro-survival Pim-1

Abstract: BackgroundDiabetic women are five times more likely to develop congestive heart failure compared with two fold for men. The underlying mechanism for this gender difference is not known. Here we investigate the molecular mechanisms responsible for this female disadvantage and attempt safeguarding cardiomyocytes viability and function through restoration of pro-survival Pim-1.Methods and ResultsDiabetes was induced by injection of streptozotocin in CD1 mice of both genders. Functional and dimensional parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 41 publications
6
39
1
Order By: Relevance
“…Some of the inconsistencies associated with for example protein expression levels may be associated with the size and frequency of the STZ dose, route of administration and the interval after injection that the animals are examined. Interestingly, a recent report has also shown that the development of cardiomyopathy, in the STZ female rat is more rapid than in the aged-matched male (Moore, et al, 2014); mirroring the human diabetic female predisposition to a higher mortality as described in the introduction. In addition to the STZ/alloxan models there are several genetically derived T1DM mouse models such as the Akita mouse (Ins2 Akita ) and the OVE26 mouse (Song, Du, Prabhu, & Epstein, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 80%
See 1 more Smart Citation
“…Some of the inconsistencies associated with for example protein expression levels may be associated with the size and frequency of the STZ dose, route of administration and the interval after injection that the animals are examined. Interestingly, a recent report has also shown that the development of cardiomyopathy, in the STZ female rat is more rapid than in the aged-matched male (Moore, et al, 2014); mirroring the human diabetic female predisposition to a higher mortality as described in the introduction. In addition to the STZ/alloxan models there are several genetically derived T1DM mouse models such as the Akita mouse (Ins2 Akita ) and the OVE26 mouse (Song, Du, Prabhu, & Epstein, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…In addition, one of the studies employed both male and female animals e.g. (Malhotra, Penpargkul, Fein, Sonnenblick, & Scheuer, 1981), which may be a contributing factor leading to inconsistencies between reports, especially given the recent study showing that the onset and progression of DCM is more rapid in the female rats (Moore, et al, 2014).…”
Section: Impaired Excitation-contraction Coupling Is a Hallmark Of DImentioning
confidence: 93%
“…To determine if high glucose also increases the necrotic cell death, we measured the level of RIP kinase, whose activation has been demonstrated to promote necrotic cell death in the heart. [28,29] As shown in the supplemental Figure 3, there was no significant change in the expression pattern of RIP following high glucose treatment for 72h. This suggest that apoptosis is the major form of cell death in our experimental model.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Ryanodine receptor Ca 2+ release channel complex (RyR2) located in sarcoplasmic reticulum is a target proteins for miR-1 in the diabetic heart, and exerts a vital role in Ca 2+ transport and cardiomyocyte contractility [84]. Moreover, miR-1 targets the 3′UTRs of MEF2A, transcription factor GATA binding protein 4 (GATA4), and other key cardiac-specific transcriptional factors such as heart and neural crest derivatives expressed 2 (Hand2), all of which exhibit essential role in myocardial differentiation, development and function [8587]. MiR-208a, one of a positive regulator of hypertrophy is a cardiac-specific miRNA, and a possible inhibitor of Pim-1 expression [87].…”
Section: Mirna Modulation In Cardiac Hypertrophy and Fibrosismentioning
confidence: 99%
“…Moreover, miR-1 targets the 3′UTRs of MEF2A, transcription factor GATA binding protein 4 (GATA4), and other key cardiac-specific transcriptional factors such as heart and neural crest derivatives expressed 2 (Hand2), all of which exhibit essential role in myocardial differentiation, development and function [8587]. MiR-208a, one of a positive regulator of hypertrophy is a cardiac-specific miRNA, and a possible inhibitor of Pim-1 expression [87]. Overexpression of miR-208a leads to repression of myostatin and GATA4, as well as upregulation of β-myosin heavy chain (MHC) that contributes to cardiac hypertrophy [41, 54].…”
Section: Mirna Modulation In Cardiac Hypertrophy and Fibrosismentioning
confidence: 99%